KARAKTERISTIK IBU DENGAN KEJADIAN GIZI KURANG PADA BAYI 6-24 BULAN DI WILAYAH KERJA KELURAHAN TANJUNG UNGGAT - Sara Munthe, Atika; Nababan, Tiarnida; Suryani Harahap, Efi; Wahyuni, Dwi; Priastika, Awaluci; Efriyanisari, Efriyanisari (NHM PRESS, 2025)
Children under 5 years old (infants) are in their golden age. Children at this age grow rapidly and need to be fed on demand. Children who get the right nutrition and according to their needs will grow and develop optimally and develop into quality human resources. Children at this age are vulnerable to nutritional problems. Nutrition is a measure of a person's physical condition and is determined by the food we eat and how the nutrients are used by the body. Objective To determine the characteristics of mothers with cases of malnutrition in infants aged 6-24 months in the Tanjung Unggat sub-district work area. The research method is descriptive observational and analyzed univariately and bivariately using the chi square test. Results The nutritional status of toddlers is mostly lacking (68.75%) The education level of mothers is mostly high school (50%). The employment status of mothers is mostly unemployed (53%). The results of the chi-square test analysis show that the p value for the mother's age with the nutritional status of toddlers is 0.022, the p value for the mother's education level with the nutritional status of toddlers is 0.001, the mother's employment status with the nutritional status of toddlers is 0.003. Conclusion: There is a relationship between age, maternal education level, maternal occupation and nutritional status of toddlers.